Modeling biological systems a unified approach. - Darbari, Manuj
In this paper we demonstrate the relevance of abstraction, reuse, objects, classes, component and inheritance hierarchies, multiplicity, visual modeling, and other current software development best practices. We show how it is possible to start with a direct diagrammatic representation of a biological structure such as a cell, using terminology familiar to biologists, and by following a process of gradually adding more and more detail, arrive at a system with structure and behavior of arbitrary complexity that can run and be observed on a computer. We will be discussing various tools of UML used to describe biological modeling.
Keywords: Computer applications; Life and medical sciences; Biology and genetics; Software; Programming techniques; Object oriented programming; Software engineering; Design tools and techniques; Design; Languages; UML; Agent-based modeling; Cell simulation